Analisis Usaha Budidaya Pembesaran Ikan Nila Secara Intensif Dengan Sistem Bioflok : Studi Kasus Pada Nugraha Fishery Di Kecamatan Mangkubumi (International Forum of Researchers and Lecturers, 2023)
Tilapia is one of the fisheries commodities in Indonesia. Tilapia fish has a high market demand, therefore the supply of tilapia fish should continue to be fulfilled, but the supply of tilapia fish in the market is still not enough. In order to the demand for tilapia fish can be met, there are several ways to increase tilapia production. One of the methods to cultivate Tilapia is using biofloc cultivation. One of the biofloc tilapia aquaculture entrepreneurs in Tasikmalaya city is Mr. Banyu who is the owner of Nugraha Fishery. This research aims to analyze production cost and income as well as business feasibility in running biofloc tilapia cultivation. The research was conducted at Nugraha Fishery which is located in Cipari Village, Mangkubumi District, Tasikmalaya City. The results of this research showed that the business feasibility criteria used in intensive tilapia cultivation with biofloc include: NPV, IRR, PP, Net B/C ratio. Net Present Value NPV is Rp. 217,754,348, IRR Internal Rate of Return value of 44%, PP Payback Period value of 4.2 years, Net B/C Ratio value of Rp. 2.9. All business feasibility criteria stated that it is feasible, meaning that the intensive tilapia cultivation business with biofloc which is run by Nugraha Fishery in Cipari Village, Mangkubumi District, Tasikmalaya City is suitable to be run and developed.